Internet of Things (IoT) Based Fire Detection and Suppression System - Dienatu Issaka; Yaw Amankrah Sam-Okyere; Emmanuel Osei-Kwame (Applied Engineering, Innovation, and Technology, 2025)
Fire incidents cause significant threats to life and property, particularly in critical infrastructure. This research presents the design and implementation of an Internet of Things (IoT)-based fire detection and suppression system featuring real-time monitoring and scalable sensor integration. The system integrates an ATmega328p microcontroller, RF transceivers, flame and smoke sensors, NodeMCU (ESP8266), solenoid valves, relays, a jockey pump, and water sprinklers. Sensor fusion ensures high detection accuracy, triggering suppression only upon simultaneous smoke and flame detection to minimize false positives. Communication between transceivers controls the pump operation, while the NodeMCU transmits sensor data to a remote web server via Wi-Fi for continuous monitoring. When a fire is detected by the sensors, the controller promptly activates the fire alarm system, which in turn triggers the jockey pump to discharge water through the sprinkler system at the affected locations.